Characterization of groundwater dynamics in landslides in varved clays - J. E. van der Spek; T. A. Bogaard; M. Bakker (Hydrology and Earth System Sciences, 2013)
Groundwater dynamics may play a significant role in landslides. A detailed model is developed of the groundwater dynamics in landslides in varved clays in the Trièves area in the French Alps. The varved clays consist of a sequence of alternating silt and clay layers, covered by a colluvium layer and intersected by fissures. The hydraulic conductivity of the clay layers is negligible compared to the silt layers. It is conceptualized that fissures form a hydraulic connection between the colluvium and the varved clays. Groundwater recharge flows through the colluvium into the fissures, where water is exchanged horizontally between the fissure and the silt layers of the varved clays. Groundwater flow in the colluvium is simulated with the Boussinesq equation, while flow in the silt layers of the varved clays is simulated with the Richards equation. Longitudinal outflow from the fissure is simulated with a linear-reservoir model. Scattered data of relatively short monitoring periods is available for several landslides in the region. A good similarity between observed and simulated heads is obtained, especially when considering the lack of important physical parameters such as the fissure width and the distance between the monitoring point and the fissure. A simulation for the period 1959–2004 showed some correlation between peaks in the simulated heads and the recorded occurrence of landslides, while the bottom of the varved clays remained saturated during the entire simulation period.